Metal concentrations in Sungai Sedili Kecil, Johor, Peninsular Malaysia - Shuhaimi-Othman, M; Ahmad, A.K; Nadzifah, Y; Azmah, M (University Kebangsaan Malaysia, 2012)
Water and sediment from five sampling stations in Sungai Sedili Kecil were sampled in October 2010 and analyzed for 11 metals including cadmium (Cd), copper (Cu), manganese (Mn), iron (Fe), lead (Pb), aluminium (Al), zinc (Zn), nickel (Ni), cobalt (Co), arsenic (As) and argentum (Ar). Results showed that the mean dissolved metal concentrations (in μg/L) in Sungai Sedili waters based on 5 sampling stations (in descending order) for Fe, Al, Zn, Cu, As, Mn, Ni, Pb, Co, Cd and Ag were 443.7, 52.7, 50.2, 34.2, 25.9, 20.3, 6.8, 1.4, 0.77, 0.67 and 0.10 μg/L, respectively. Mean metal concentrations (in μg/g dry weight) for sediments (in descending order) for Fe, Al, Mn, Zn, Pb, Cu, As, Ni, Co, Cd and Ag were 33389.4, 17118.7, 190.5, 55.1, 29.1, 26.3, 19.3, 10.9, 4.7, 0.18 and 0.12 μg/g, respectively. A comparison with various water and sediment quality standards showed that the mean metal concentrations in surface water and sediment of Sungai Sedili Kecil were low and within the range of natural background except for Cu and Fe in water.